(untitled) (Bangladesh Journal of Public Administration, 2022)
Through various forms of support, in Bangladesh, safety net programs have been able to reach a variety of population segments and help decrease poverty and vulnerability. Every year, to reduce poverty and hardship among the populace, the Bangladeshi government affords a huge amount of money from the national budget. These include establishing temporary jobs for men and women of working age, providing income stability for the elderly, widows, and people with disabilities, and promoting the growth of young mothers and children. Safety net initiatives are being implemented in an increasing number of nations, and they help tackle economic inequality and protect the condition of the lowest income groups. The research was conducted with a mixed-methodology approach that combines qualitative and quantitative data analysis. The researcher used a questionnaire to gather information from a practical sample of 60 individuals of Kadirpur union, Shibchar Upazila who are getting old allowance and widow allowance. From this research, it is clear that the beneficiaries who get old allowance spend their money on buying medicine and those who get widow allowance spend most of the money on child education. Most of the beneficiaries stated this opinion that the amount of money is insufficient for them, and the fund should be increased. Inadequate funding, duplication, unauthorized political influence and coverage gaps must all be addressed. They also share their feelings that, in selecting the recipient, nepotism should be avoided and should give priority to those who truly deserve it.